2011
DOI: 10.1071/rd10279
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation against inhibin enhances follicular development, oocyte maturation and superovulatory response in water buffaloes

Abstract: This study was carried out to test the feasibility of enhancing embryo production in vivo and in vitro by immunoneutralisation against inhibin or follistatin. In Experiment 1, multi-parity buffaloes were assigned into three groups: High group (n=8), which received one primary (2mg) and two booster (1mg) vaccinations (28-day intervals) with a recombinant inhibin α subunit in 1 mL of white oil adjuvant; Low group (n=8), which received half that dose; and Control group (n=7), which received only adjuvant. Immunis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
1
36
1
Order By: Relevance
“…However, inhibin A has also been shown to exert a blocking action on the activin A and other TGFß member dependent regulation of steroidogenesis and proliferation within the ovary [16]. Immunization against inhibin can promote an increase in ovulation rate and prolificacy [40] through enhanced follicular development in sheep [41], goat [42] and water buffalo [43]. It has been suggested that inhibin antibodies may act primarily by an intraovarian paracrine action rather than by reducing the suppressive action of inhibin on pituitary FSH release [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibin A has also been shown to exert a blocking action on the activin A and other TGFß member dependent regulation of steroidogenesis and proliferation within the ovary [16]. Immunization against inhibin can promote an increase in ovulation rate and prolificacy [40] through enhanced follicular development in sheep [41], goat [42] and water buffalo [43]. It has been suggested that inhibin antibodies may act primarily by an intraovarian paracrine action rather than by reducing the suppressive action of inhibin on pituitary FSH release [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…Passive and active (Ishigame et al, 2004) immunization against inhibin results in increased pituitary secretion and plasma concentrations of FSH, which could stimulate follicle development and improve the ovarian response to superovulation, resulting in increased ovulation rates and higher yields of transferable embryos in sheep (D'Alessandro et al, 1999), heifers or cows Mei et al, 2009), and water buffalo (Li et al, 2011). Due to the important role of inhibin in FSH secretion and as a growth factor in the ovary, INHβA was confirmed to be an important candidate gene for improving reproductive performance (Xue et al, 2004;Phillips, 2005;Chu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of its inhibitory action on FSH secretion, inhibin has been widely used in the treatment of superovulation. Previous studies have demonstrated that immunization against inhibin could improve the ovarian response to superovulation, resulting in increased ovulation rates and higher yields of transferable embryos in sheep (D'Alessandro et al, 1999), heifers or cows Mei et al, 2009), and water buffalo (Li et al, 2011). Therefore, inhibin is a potential candidate gene for superovulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many other cases inhibin has been produced in mammalian cells [16, 92]. Importantly, recombinant inhibin has been used as an antigen for the immunization against endogenous inhibin in hens [93, 94], cockerels [95], heifers [87, 89, 96], water buffaloes [88], guinea pigs [97], goats [98], and sheep [99102]. Only in a minority of cases, the recombinant inhibin α subunit used is obtained synthetically [103106] or purified from follicular fluid [107].…”
Section: Recombinant Hormones In Reproductionmentioning
confidence: 99%